PENGARUH SOCIAL MEDIA MARKETING DAN PROMOSI HARGA TERHADAP KEPUASAN KONSUMEN DAN PENGALAMAN KONSUMEN SEBAGAI VARIABEL MEDIASI PADA MASKAPAI PENERBANGAN AIRASIA DI BANDA ACEH - Deva Fajri, Jasman J Ma’ruf (Departemen Manajemen, 2018)
Abstract: This study aims to measure the influence of Social media marketing and Price Promotion on Consumer Satisfaction and Consumer Experience as a mediation variable on AirAsia airlines in Banda Aceh. The sample used in this study is the population of Banda Aceh city which amounted to 150 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Purposive Sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved. Based on the results of the HLM analysis indicated that social media marketing positively influence consumer satisfaction, price promotion positively influence consumer satisfaction, social media marketing positively influence consumer experience, price promotion positively influence consumer experience, consumer experience positively influence consumer satisfaction, consumer experience mediate the relationship between social media marketing and consumer satisfaction, and consumer experience mediate the relationship between price promotion and consumer satisfaction.